INVESTMENT DECISIONS ON THE CRYPTOCURRENCY MARKET AND THEIR IMPACT ON THE COUNTRY’S FINANCIAL SECURITY - Sloboda , Larysa; Rodionova , Evelina (Socio-economic relations in the digital society, 2021)
The article substantiates the impact of the investment component on the financial security in terms of digitalization investment decisions in the COVID-19 period. Developed the content of investment security from the standpoint of changing investment capital, which was previously invested at modernization of national economy. It is proved that such an inflow of capital poses a significant threat to the financial security. The virtual form of investment potential at the choice of investors, guided by the motives of effective investment, creates risks to the stability of national finances. The analysis of tendencies and investment decisions in the market of cryptocurrencies and virtual exchanges is carried out, the basic subjects of investment safety in this sphere and their motives concerning investment activity are defined taking into account regulatory aspect and ways of entrance of private investors in the market of virtual investments. The significant threat to the country’s financial security is the implementation of investment decisions with cryptocurrencies based on decentralized (virtual) financial platforms (DeFi), in which neither central banks nor governments have the power of regulation. The solution of the situation of confrontation of centralized and decentralized finances in the field of investment decisions on the basis of their mutually beneficial integration is offered. It is proved that in Ukraine there is a need to create an appropriate legal framework for cryptocurrencies to bring numerous cryptocurrency projects into the legal field and allow them to interact with traditional financial service providers for transferring innovation and knowledge. The state policy on investment promotion should take into account the factors of globalization and the new technological system, because fintech is able to generate innovative tools to attract financial resources, which is necessary for Ukraine in the context of finding alternative financial sources. Prospects for further exploration will be aimed at finding effective ways to integrate traditional financial and virtual investments to increase the financial security of the national economy in the modern digital age.